A dataset of color QR codes generated using back-compatible and random colorization algorithms exposed to different illumination-capture channel conditions - Ismael Benito-Altamirano; David Martínez-Carpena; Olga Casals; Cristian Fàbrega; Andreas Waag; Joan Daniel Prades (Data in Brief, 2023)
Color QR Codes are often generated to encode digital information, but one also could use colors or to allocate colors in a QR Code to act as a color calibration chart. In this dataset, we present several thousand QR Codes images generated with two different colorization algorithms (random and back-compatible) and several tuning variables in these color encoding. The QR Codes were also exposed to three different channel conditions (empty, augmentation and real-life). Also, we derive the SNR and BER computations for these QR Code in comparison with their black and white versions. Finally, we also show if ZBar, a commercial QR Code scanner, is able to read them.